Some parasites of the yellow-finned sea bream Acanthopagrus latus (Houttuyn, 1782) in the Iraqi marine waters - Al-Daraji, Salem A.M.; A.Bannai, Majid A.; Abbas, Abbas A.K. (Iraqi Journal of Aquaculture, 2022)
A total of 34 fishes, belonging to the yellow-finned sea bream Acanthopagrus latus were collected, in April 2008 from Khor Abdullah northwest Arabian Gulf, by using trawler net. Fishes were surveyed for parasites. The study revealed the presence of two species of parasites the first one is a monogenetic trematode, Polylabris mamaevi and the second is a digenetic trematode, Paradiscogaster farooqii. The detection of P. farooqii in the present study represents its first record in the fishes of the Iraq.